2007
DOI: 10.1017/s148180350001486x
|View full text |Cite
|
Sign up to set email alerts
|

Airway management in penetrating neck trauma at a Canadian tertiary trauma centre

Abstract: Objectives: The optimal approach to airway management in penetrating neck injuries (PNIs) remains controversial. The primary objective of this study was to review the method of endotracheal intubation in PNI at a Canadian tertiary trauma centre. Secondarily, we sought to determine the incidence of PNI in our trauma population and to describe the epidemiologic elements of this population. Methods: We conducted a review of patients with PNIs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…[1][2][3] PNI can result from stab wounds, gunshots, or, less commonly, trauma due to other sharp objects, such as glass. In the United States, PNI comprises about 1% of all trauma patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] PNI can result from stab wounds, gunshots, or, less commonly, trauma due to other sharp objects, such as glass. In the United States, PNI comprises about 1% of all trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 A single-centre review suggests that PNIs are less common in Canadian major trauma centres (about 0.5%), which may reflect the comparatively lower rate of violent crime. 3 In a systematic review involving over 2,400 patients with PNI, McConnell and Trunkey reported that the vital structures involved in such injuries included the trachea (10%), esophagus (9.6%), internal jugular veins (9%), and carotid arteries (6.7%). 5 Overall mortality in patients with PNI ranges from 3 to 10%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nova Scotia has a provincewide population based trauma system which includes one adult (≥ 16 years) tertiary trauma centre (the study site) similar to a level I American trauma centre in many ways and the registry has been successfully used in other peer reviewed published research. 18,20,23 This project employed secondary analysis of an existing database, and involved no patient contact, treatment or chart reviews. Simple descriptive statistics were utilized to describe trends in the use of DPL, CT and FAST as diagnostics tools to evaluate these patients.…”
Section: Methodsmentioning
confidence: 99%